Hydatid cyst of the pancreas: A case report and brief review - İbrahim MASOODI and Ghulam NABI and Rakesh KUMAR and Mushtaq Ahmad LONE and Bilal Ahmad KHAN and Khalid NASEER AL SAYARI (Turkish Journal of Gastroenterology, 2019)
-